2020
DOI: 10.1111/risa.13478
|View full text |Cite
|
Sign up to set email alerts
|

A Dominance‐Based Rough Set Approach for an Enhanced Assessment of Seasonal Influenza Risk

Abstract: Accounting for about 290,000–650,000 deaths across the globe, seasonal influenza is estimated by the World Health Organization to be a major cause of mortality. Hence, there is a need for a reliable and robust epidemiological surveillance decision‐making system to understand and combat this epidemic disease. In a previous study, the authors proposed a decision support system to fight against seasonal influenza. This system is composed of three subsystems: (i) modeling and simulation, (ii) data warehousing, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…The advantage of producing vulnerability maps means that places that have been subject to previous pandemics and their risks (UNISDR, 2009;Hazarika et al, 2018) can be identified in addition to a multidimensional comprehension of social, economic, ecological and geographical factors. However, there are many aspects related to the current context (Adger, 2006;Younsi et al, 2020), which led us to construct a decision-learning model to identify areas vulnerable to COVID-19 using, simultaneously, demographic variables associated with the occurrence of the disease, including space characteristics and transmission dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of producing vulnerability maps means that places that have been subject to previous pandemics and their risks (UNISDR, 2009;Hazarika et al, 2018) can be identified in addition to a multidimensional comprehension of social, economic, ecological and geographical factors. However, there are many aspects related to the current context (Adger, 2006;Younsi et al, 2020), which led us to construct a decision-learning model to identify areas vulnerable to COVID-19 using, simultaneously, demographic variables associated with the occurrence of the disease, including space characteristics and transmission dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…On the scientific front, recent research has contributed to improved health capabilities. Initiatives include the development of decision support systems to increase the surveillance of health capability (Younsi et al., 2019; Younsi et al., 2020), the use of portfolio decision analysis to evaluate and improve capabilities of health security systems (Del Rio Vilas et al., 2013), and extensive discussions about the capabilities needed to face priority emerging and reemerging infectious diseases and to strength global health security systems (Ross et al., 2015). Other studies have focused on a specific health capability.…”
Section: Introductionmentioning
confidence: 99%